3D-MTF of Computed Tomography (CT) Images Using a 3D-Wire Phantom: The Impact of Tube Voltage Variations (International Journal of Scientific Research in Science and Technology, 2024)
Key exposure factors, such as tube voltage are critical in CT examinations as they will impact the quality of the images produced by the CT scan. Spatial resolution is one of the parameters that can be used to determine image quality. The purpose of this study is to evaluate the impact of tube voltage in spatial resolution in three axes (x, y, z) using an in-house wire phantom. The results show that MTF 10% in the axial plane (x-y) is approximately identical (approximately 0,70 mm) for various tube voltages 80, 100, 120, and 140 kV. The same results were observed at the coronal and sagittal plane (z-axis), although they exhibit more variation than axial plane the differences in values between tube voltages are not significant.